2006
DOI: 10.1021/ic0515047
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic Cu(II) Dipyrromethene Complexes Linked via Hydrogen Bonds, Coordinative Bonds, and Covalent Bonds:  Probing the Coordination Environment by Electron Paramagnetic Resonance Spectroscopy

Abstract: meso-Phenyldipyrromethene acetylacetonato copper(II) complexes [Cu(dpm-C6H4R)(acac)] (dpm-C6H4R = phenyl-substituted dipyrromethene, acac = acetylacetonato) with different substituents R at the phenyl moiety were synthesized. These substituents determine the mode of assembly into polymeric chains, namely, via hydrogen bonds, coordinative bonds, or covalent bonds (by immobilization on a polymer). Although the primary coordination sphere around the copper center is essentially identical for all complexes reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 43 publications
8
23
0
1
Order By: Relevance
“…The reaction is finished within minutes. EPR spectroscopy [16] confirms the formation of the immobilised ferricinium cation as the typical axial pattern with g ʈ = 4.30 and g Ќ = 1.99 is observed. [17] Chemical reversibility is checked on-bead by re-reduction to the neutral peptides employing CoCp 2 as reductant and UV/Vis-spectrophotometric monitoring (disappearance of the 512 nm band of CoCp 2 and development of the 400 nm absorption band of [CoCp 2 ] + ).…”
Section: Electrochemistry Of Ferrocene-containing Peptidessupporting
confidence: 57%
“…The reaction is finished within minutes. EPR spectroscopy [16] confirms the formation of the immobilised ferricinium cation as the typical axial pattern with g ʈ = 4.30 and g Ќ = 1.99 is observed. [17] Chemical reversibility is checked on-bead by re-reduction to the neutral peptides employing CoCp 2 as reductant and UV/Vis-spectrophotometric monitoring (disappearance of the 512 nm band of CoCp 2 and development of the 400 nm absorption band of [CoCp 2 ] + ).…”
Section: Electrochemistry Of Ferrocene-containing Peptidessupporting
confidence: 57%
“…OAT from the polymer-anchored Mo(L 5 ) 2 (O) 2 to PMe 3 gives soluble OPMe 3 as shown by 31 [81]. All EPR spectra of these immobilized Mo V complexes are anisotropic even in the solvent-swollen state of the polymer suggesting a severely reduced mobility of the doubly-anchored species as compared with singly-anchored complexes [134]. The anisotropy renders observation of 95 95 Mo and thus further ascertains the presence of Mo V [81].…”
Section: O] 2 ( -O) or [Mo(l)o] 2 ( -O) 2 ( -Thf)mentioning
confidence: 80%
“…We have previously shown that singly polymer attached Cu II complexes give isotropic EPR spectra under gel-phase conditions suggesting that a single-point attachment allows for sufficient mobility. [34] However, two-point fixation seems to decrease the mobility of the anchored complexes 4b resulting in anisotropic EPR spectra even in the gel-phase at room temperature. [35] In addition this finding proves that the molybdenum species are still bound to the support as otherwise isotropic signals for soluble species would have been observed.…”
Section: Methodsmentioning
confidence: 99%